Suggestions for the Medical Experts in Custody Deaths - Sudha, R; Siddiqui, M A Mujeeb; Kumar, D Sravan; Kumar, N Rupesh; Jayasurya; Kiran, A Kranthi (Journal of Indian Academy of Forensic Medicine, 2015)
Human death itself is an untoward and unfortunate one for all near and dear ones. Component of  unexpectedness specially raises suspicion among relatives, media and community. Deaths in police  custody is among the major chunk of such deaths even though low in terms of incidence but having  heavy potential of creating major hue and cry. A retrospective study of custodial deaths in various police  stations of Andhra Pradesh from 1978 to 1999 was conducted. In spite of diverse difficulties encountered,  records of 90 cases could be gathered from various sources like Legal cell of DGP‟s office, from report of  various commission of Inquiry which are available in the library of A.P. Assembly. An attempt was made to review administrative and medico-legal aspects of 90 cases with regards  to circumstances of death, various causes of death, nature of death and lapses on the part of the doctors  involved in such cases has been made in the present study. Various suggestions are also put forward in  the judicial commission to prevent recurrence of such deaths. To the best of our belief and knowledge,  such study are very far and few off in bio medical literatures in India.
Keywords: Custodial Death; Medico-legal; Police